A Cross-National Examination of School Violence and Nonattendance Due to School Violence in Taiwan, Hong Kong, and Mainland China: A Rasch Model Approach. (2nd April 2020) - Chen, Ji-Kang; Chen, Li-Ming
ABSTRACT: This study examined the similarities and differences between three distinct Chinese societies (Taiwan, Hong Kong, and China) regarding the contribution of gender and grade level to school violence, the ranking orders of perpetration and victimization behavior, and the correlates of school nonattendance due to violence. A cross-national random sample of 2, 582 junior high school students was obtained. The results of Rasch analyzes revealed that verbal violence is most frequent. Male students are most likely to be aggressive and victimized. Grade-level differences in school violence were shown to be weak or insignificant. School nonattendance is generally associated with being kicked, punched, socially excluded, blackmailed, threatened, or sexually kissed without consent. The results were similar across societies. The findings imply that the contextual differences between Chinese societies may not account for different effects of gender and grade level on school violence, behavioral patterns of school violence, and correlates of school nonattendance.